Evaluating Internal Democratic Process in Political Parties: A Case Study of PDI-P in the Reform Era - Subekti, Dimas; Putra, Dinda Syufradian; Nasuhaidi, Nasuhaidi (Universitas Medan Area, 2025)
This research aims to explain the internal democratic process of the Indonesian Democratic Party of Struggle (PDIP). The novelty contribution of this research is that it focuses on the internal democracy of political parties from the point of view of the process. This type of research is qualitative and uses a case study approach. This research finds that the recruitment of leadership parties does not apply the principles of democracy properly. This process has no room for competition because it is too elite-dominated. Then, the decision-making mechanism is centered on the general Chairman, so the involvement of cadres is minimal. Furthermore, the Indonesian Democratic Party of Struggle has a conflict resolution mechanism with a party court. However, the institution needs to be more independent to resolve conflicts within the Party. In the principle of democracy, all are equal before the law. Thus, the internal democracy of the Indonesian Democratic Party of Struggle is undergoing changes whose impact can jeopardize the survival of the Party itself in the long run because it is vulnerable to political clashes. Then, this research argues that political parties with strong and charismatic leadership are vulnerable to the failure of their internal democratic processes. This has resulted in the emergence of pseudo-powers in political parties and threatens their solidity in the long run.